Explaining the attainment of the second-generation: When does parental relative education matter? - Alessandro Ferrara; Renee Luthra (Social Science Research, 2024)
How can we understand unexplained variation in the educational outcomes of the children of immigrants? A growing literature posits that standard educational transmission models fail to explain national origin differences in attainment because they ignore immigrant selectivity – the degree to which immigrants differ from non-migrants in their sending countries. The immigrant selectivity hypothesis is usually tested using indicators of parents' relative or “contextual” educational attainment, measuring their rank in the educational attainment distribution of their country of origin. However, using this proxy, current support for the hypothesis is mixed. We outline three conditions for the use of educational selectivity as a proxy for relative social positioning among the children of immigrants. We test our conditions using an adult and a youth sample from a large household panel survey in the UK. We supplement our analyses by exploring relative education data from prior research on Italy, France and the United States. Triangulating these varied sources, we illustrate cases when our three conditions do and do not hold, providing evidence from the UK and other contexts. We provide guidelines on the use of relative education as a measure of relative social standing in cross-national research as well as an assessment of the immigrant selectivity hypothesis in explaining second-generation educational outcomes.
Keywords: 320; Immigrant selectivity; Relative education; Immigrant paradox; Second generation